Mapping social movements momentum: unveiling networks in the movement for the right to abortion in Mexico - López Martínez, Cesángari; Sambo, Allison; Medina González, Diana (Frontiers in Research Metrics and Analytics, 2024)
In this case study, we propose a network analysis approach to map social movements through an intersectional feminist lens. We aim to gain a more in-depth understanding of movements’ network structures to examine the roles and relationships of movement actors, the flow of resources between them, and potential areas of collaboration and conflict. By incorporating Social Network Analysis (SNA) techniques and visually mapping dynamics within social movements, this approach can assess the significance of small actors in creating change and stresses the need for their perspectives to be heard. Furthermore, our methodology adopts a feminist intersectional framework that recognizes the role of different identities in shaping the movement and its actors. To demonstrate the practical application of this approach, we examined the movement for the right to abortion in Mexico between September and December 2021. Our multi-step process included 1) designing a survey tool adapted to the context of the movement, 2) collecting and analyzing survey responses on movement actors’ relationships and interactions, including their priorities, activities, needs, risks, and challenges, 3) visualizing the network using SNA techniques that account for the complexity and diversity of the movement, 4) interpreting the findings through insights collected in semi-structured interviews and validation meetings with key movement actors, and 5) implementing safety and security guidelines to safeguard the identity of individuals whose activities could put them at risk of suffering institutional, emotional, and physical violence. Our case study offers valuable insights that not only encourage the integration of feminist and intersectional perspectives into data collection processes but also provide a roadmap for accompanying social movements and supporting meaningful and contextually responsive activities.